DEVELOPMENT OF VIDEO GAME-BASED EDUCATIONAL MEDIA AS AN EFFORT TO PREVENT SEXUAL VIOLENCE IN ELEMENTARY SCHOOL CHILDREN - Eviana Sumarti Tambunan; Ratna Ningsih; Tharisa Liani; Titi Sulastri; Dina Carolina Hapsari (Jurnal Keperawatan, 2026)
Sexual violence against children is a serious issue that impacts their psychological, social, and cognitive development. The lack of early sexual education, coupled with societal views that consider this topic taboo, increases children's vulnerability to becoming victims. With technological advancement, educational media in the form of video games has emerged as an engaging and promising alternative to enhance children's knowledge of sexual violence prevention. Objective: To develop an educational video game and evaluate its effectiveness as a tool for preventing sexual violence among elementary school children. This study employed a Research and Development (R&D) design with a one-group pretest-posttest approach without a control group. A total of 90 students from grades 3 to 5 were selected through stratified random sampling. Research instruments included pretest and posttest knowledge questionnaires, as well as a media feasibility assessment questionnaire. Data analysis using the Wilcoxon test showed that the average knowledge score increased from 7.01 before the intervention to 10.61 after the intervention. The results indicated a significant improvement in children's knowledge after using the educational media (p < 0.05). Furthermore, the feasibility assessment revealed that the video game was rated as "highly feasible" by users as an educational tool. The educational video game is both effective and feasible as a tool for teaching sexual violence prevention to elementary school children. It also supports parents and teachers in delivering sensitive material through an enjoyable and interactive approach.